Prediction of nuclear grade of clear cell renal cell carcinoma with MRI: intratumoral susceptibility signal intensity versus necrosis. (April 2014) - Chen, Jie; Sun, Jun; Xing, Wei; Ding, Jiule; Chen, Tongbing; Dai, Yongming; Sun, Jingyi; Hu, Jiani
Background: End-stage renal disease and dialysis patients have a higher incidence of renal cell carcinoma (RCC) than the general population. Preoperatively evaluating the biological behavior of RCC plays an important role in treatment decision-making. Susceptibility-weighted imaging (SWI) can visualize the distribution of microvenous structures and hemorrhage without contrast materials. Purpose: To evaluate the feasibility of SWI in grading clear cell RCCs (CRCC) and compare the ability of SWI and necrosis for grading CRCCs. Material and Methods: Retrospective reviews of 35 patients with pathologically-proven CRCCs were performed. All patients underwent both conventional magnetic resonance imaging (MRI) and SWI examinations. The morphology of the intratumoral susceptibility signal intensities (ITSS) was classified into hemorrhage and microvessels. The differences of ITSSs on SWI and necrosis between low- and high-grade CRCCs were assessed. The diagnostic values of ITSSs and necrosis in differentiating low- from high-grade CRCCs were compared by receiver-operating characteristics. Results: ITSSs were seen in 31 of 35 patients. No ITSSs were seen in four patients with low-grade CRCCs. Mean scores of ITSSs on SWI were significantly lower for low-grade CRCCs (1.24 ± 0.72) than that for the high-grade CRCCs (2.70 ± 0.48). No significant necrosis was seen in 10 patients with low-grade CRCCs. There was a significant difference of the presence of intratumoral necrosis between low- and high-grade CRCCs. Sensitivity, specificity, positive (PPV) and negative predictive values (NPV) were for ITSSs: 70%, 100%, 100%, and 89.3%, respectively; for necrosis: 100%, 40%, 40%, and 100%. Conclusion: SWI can evaluate ITSSs without contrast materials and can be an alternative to grading CRCCs preoperatively for some special patients.